DINAMIKA TULISAN ARAB - Tamrin . (Program Studi Ilmu Al-Qur'an dan Tafsir, Institut Agama Islam Negeri (IAIN) Palu, 2020)
In writing, the Arabic letter is the second letter after the Latin letter which continues to develop and exist today. However, the delay in its development is strongly influenced by the Arab social tradition which prioritizes verbal language and wandering life. In the pre-Islamic era, especially in the 6th century, linguistic activities were dominated by literature rather than written development. After Islam came the people called for writing the revelations, a spirit of writing began and continued to develope.